(untitled) (Altre Modernità, 2013)
If apocalypse is a metaphor of the end and the beginning of an age, collapse of cultural, political and social concepcions, construction of new identities and social realities, literature of “frontera norte de México” is good to realize an investigation of the biblical and mythical theme in postmodern sence. Colapsing any idea of legal and civil life in a national State, urban culture of “la Frontera” presents the social caos of ilegal and criminal conducts, as much es gendre violence and the political idea of national identity in crisis. México protagonize a contradiction between nacionalist pride, frontier defence and emigration to the Unites States, with apocalyptical implication these days. The narrative of Luis Humberto Crosthwaite permit to analyze the different representations of broken identity in the social caos of the frontier. The apocalypsis as inminent catastrophe, social insicurity and uncertain identity leads the individual to new urban and social representations.